(untitled) (Baltic Journal of Sport and Health Sciences, 2021)
Background. Pre-school age is the period of especially fast growth and physical development, characterized by an intensive growth and development of a child’s organism, great changes in the activity of the functional systems, which is affected by increasing physical activeness and fitness (Grinienė & Vaitkevičius, 2009; Howells & Sääkslahti, 2019). Previous studies have identified parental influence as a factor that can shape a child’s physical self–perception and act as a stimulus for physical activity and fitness (Eddolls, McNarry, Stratton, & Mackintosh, 2016). The aim of this study was to indicate physical activity of 5–6-year-old children and to determine the interaction between parents’ physical activity and physical fitness data. Methods. The study involved pre-school age children (n = 59) from 5 to 6 years old: 31 girls and 21 boys; also, their parents (n = 101) were involved: 57 mothers and 44 fathers. Physical activity was measured objectively using the ActiGraph GT3X model. The children performed five physical fitness tests (PFT) according to the Eurofit methodology. Also, parents were asked to fill in questionnaires about their own and their children’s physical activity, and also subjective physical fitness. Results. It turned out that there was a significant difference in the time spent in moderate and moderate to vigorous (MVPA) physical activity between 5 to 6-year-old children (p < .05). Comparing pre-school children’s physical fitness by gender we found that boys were more physically fit than girls when performing long jumps, but girls were more physically fit than boys when performing a sit and reach test (p < .05). Subjectively measured PA identified that 72.6% of parents (of both genders) were sufficiently physically active and 27.4% were inadequate physically active. Conclusion. The results revealed that 6-year-old children spent more time in sedentary time than 5-year-olds, who accumulated more time in moderate and total MVPA physical activity per day. No significant relation was found between parents’ and children’s physical activity and fitness. Keywords: physical activity, physical fitness, pre-school child, health, parents.